Profil Lipid dan Kejadian Hipertensi pada Pria Perokok Berat : Lipid Profile and Hypertension Incidence in Heavy Smoking Men - Yonrizal Nurdin (Fakultas Keperawatan Universitas Andalas, 2011)
The cigarette will lead to peripheral vasoconstriction of the blood vessels and vessels in the kidneys, leading to an increase in blood pressure. Smoking every day will improve the systolic pressure by 10–25 mmHg and increase heart rate by 5–20 beats per minute. Early screening profiles of lipids include the examination of total cholesterol, low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglycerides. This examination is indispensable for detecting dyslipidemia associated with coronary heart disease. This research was conducted in Kelurahan Batang Arau, within the work areas of Pemancungan Health Center, Padang. The research design was descriptive and aimed to describe the object in accordance with its current state. The population in this research comprised all male heavy smokers aged above 40 years in Kelurahan Batang Arau, within the work areas of Pemancungan Health Center, Padang, totaling 64 people. The conclusions of the research indicated that 28.1% of respondents had values above normal, 53.1% had low HDL values, 14.5% had high LDL values, 25% had high triglyceride values, and 13.6% were hypertensive heavy smokers in Kelurahan Batang Arau, Kecamatan Padang Selatan, within the work areas of Pemancungan Health Center in 2011. It is suggested that heavy smokers quit smoking immediately and increase their consumption of fruits and vegetables to prevent hypertension and cardiovascular disease.